The Socio-Economic Factors Affecting the Performance of Girl Child in Mathematics: A Case Study of Kanaba Sub-Count Kisoro District. - Munyabuntu, Reuben (Kabale University, 2023)
The aim of the study was to examine the socio-economic factors affecting the performance or girl child in Mathematics education. The study was guided by the following objectives, to analyze and compare the boys' and girls' performance in Mathematics, to examine the socio-economic factors affecting the performance of girl child in mathematics education, to find out the ways of improving the performance of girls in mathematics. The researcher used descriptive survey design utilizing mixed research approach. The study findings show that there is influence in girl’s participation in mathematics compared to boys as they include; teachers hold the view that girls are not as trouble as boys in Mathematics as indicated by 20% respondents. beliefs lead to heavy cultural related support for males to be more successful than females as shown by 10% respondents. "parents io-economic level is thought to exercise an independent positive effect in the male. The study recommended that the school administration also needs to give the subject first priority by getting good trained and committed teachers and also show girls the importance of the subject